Kitchen cabinet cures : 1001 homemade remedies to improve your health - Kent, Samantha (Ultimo, N.S.W. : Reader's Digest, 2012)
New research is revealing the most effective ways to use ginger, lemon, spices, olive oil and hundreds of other timeless kitchen staples for health and healing, much as our grandparents once did. This practical volume includes a guide to natural medicines on your shelves, and advice on how to use kitchen staples to look and feel great.
Easy, safe, natural, effective.
Includes index.
Keywords: Self-care, Health; Health; Naturopathy